THE SOUTH CHINA SEA UNCLOS TRIBUNAL AWARD 2016: WHAT IT HAS CHANGED AND WHAT IT DOES MEAN TO INDONESIA - Agusman, Damos Dumoli (UI Scholars Hub, 2017)
Since The Permanent Court of Arbitration issued its award on 12 July 2016 it have raised many controvertion. Almost all Submissions are decided in favour of the Philippines. The Award, as expected by many scholars, is not intended to solve the core dispute of the South China Sea ‘what maritime features belong to whom’, since the very nature of this kind of dispute is not under the Tribunal competence. The sovereignty over disputed features shall be left to the claimant States for the resolution. Nevertheless, the Tribunal Award has not only clarified the dispute but also partially solve the core dispute. The legal clarification is expected to contribute to future negotiations among the claimant States concerning the core (sovereignty) dispute. This Article attempts to identify and describe what has been changed by the Tribunal Rulings and what has been solved. The implication of the Ruling on Indonesia’s legal interest is also briefly discuss.